PENERAPAN TEORI APOS UNTUK MENINGKATKAN HIGHER ORDER THINKING SKILL MAHASISWA PENDIDIKAN AGAMA ISLAM - Wahyuni, Sri; Wardana, Wardana (Atta'dib Jurnal Pendidikan Agama Islam, 2024)
This research aims to improve HOTS through the application of APOS theory to Islamic Religious Education students at IAIN Bone. This type of research is classroom action research carried out at IAIN Bone. The research subjects were 24 students of 21PAI6 Islamic Religious Education semester 5 of 2022/2023. This research consists of two cycles, namely cycle 1 and cycle II. Each cycle consists of four stages, namely planning, action, observation and reflection. The data collection techniques used are tests and observations. The results of this study indicate that HOTS has improved through the application of APOS theory. The improvement in students' HOTS abilities can be seen from the results of observations of student activities and learning outcomes obtained each cycle. Pre-action students' HOTS ability was 8.33%. In cycle I the HOTS capability increased to 50%, in cycle II the HOTS capability increased by 62.5%. The increase in student HOTS is of course also supported by real action in the form of a positive attitude that has become entrenched, interest in learning that has begun to develop and collaboration in study groups that has become entrenched.